2013
DOI: 10.1111/1753-6405.12102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of health impact assessments reported in Australia and New Zealand 2005–2009

Abstract: Objective: To describe the use and reporting of Health Impact Assessment (HIA) in Australia and New Zealand between 2005 and 2009.Methods: We identified 115 HIAs undertaken in Australia and New Zealand between 2005 and 2009. We reviewed 55 HIAs meeting the study's inclusion criteria to identify characteristics and appraise the quality of the reports.Results: Of the 55 HIAs, 31 were undertaken in Australia and 24 in New Zealand. The HIAs were undertaken on plans (31), projects (12), programs (6) and policies (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Results of several process evaluations of HIAs have been published, either alone (710) or as a combined process and impact evaluation (34,35). Guidelines are available for process evaluations (17,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of several process evaluations of HIAs have been published, either alone (710) or as a combined process and impact evaluation (34,35). Guidelines are available for process evaluations (17,50).…”
Section: Discussionmentioning
confidence: 99%
“…Process evaluations examine the process followed in conducting an HIA and compares it with the practitioner’s intended plan or with established guidelines for HIA practice (5,6); several process evaluations have been published (710). Impact evaluations examine the impacts of an HIA on selected decisions and other events; such information is valuable to those who decide whether or not to conduct HIAs.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs across the region but has been particularly prominent in Australia (Harris & Spickett ) and New Zealand (Haigh et al. ). Further discussion is also needed on the intersection between primary health care and ISA.…”
Section: Discussionmentioning
confidence: 99%
“…A process and impact evaluation of 17 case studies found that a wide variety of processes were being used by HIA practitioners in Europe (11). A 4-cell matrix for assessing HIA effectiveness developed in that evaluation was used in subsequent HIA evaluations (6,12). A process evaluation of 55 HIAs in Australia and New Zealand found that 65% of the reports that used a standard report review package were adequate (12).…”
Section: Introductionmentioning
confidence: 99%
“…A 4-cell matrix for assessing HIA effectiveness developed in that evaluation was used in subsequent HIA evaluations (6,12). A process evaluation of 55 HIAs in Australia and New Zealand found that 65% of the reports that used a standard report review package were adequate (12). An impact evaluation of 11 of those 55 HIAs found most were effective, usually by directly influencing the decision process of nonhealth-related policymakers or raising stakeholder awareness of health issues (13).…”
Section: Introductionmentioning
confidence: 99%